Fecal concentrations of lactic acid and short-chain fatty acids in young children hospitalized in an infectious-diagnostic hospital with diarrhea - O. H. Ivanko; V. M. Bilykh (Zaporožskij Medicinskij Žurnal)
The aim of the study was to investigate the fecal levels of lactic acid and short-chain fatty acids (SCFAs) in children with acute diarrhea and to identify their role in the development of infectious or non-infectious diseases.